Portugal : Third Post-Program Discussions-Press Release; Staff Report; and Statement by the Executive Director for Portugal. (IMF Staff Country Reports; Country Report ;, 2016)
This report discusses key issues related to the economy of Portugal. Highly accommodative macroeconomic conditions have generated only modest growth in the presence of remaining structural impediments. In 2015, low interest rates, a weak euro, and low oil prices remained largely in place, allowing growth to reach 1.5 percent. The 2016 budget proposal appears insufficiently ambitious to put public debt on a firmly downward trajectory, with significant risks to execution. Bank balance sheets need to be strengthened to avoid further negative surprises and protect taxpayers. Envisaged labor and product market policies imply at least a partial reversal of structural measures introduced during the IMF-supported program.